KAJIAN STABILITAS DINDING PENAHAN TANAH TERHADAP LEBAR ALAS PONDASI PADA RENCANA DINDING PENAHAN TANAH DESA MARGOMULYO KECAMATAN LOA JANAN - Salas, Joni (KURVA S JURNAL MAHASISWA, 2014)
Landslide which occurred the road that experienced landslides, must beaddressed so that it does not interfere with the performance of the road which isthe lifeblood and driving force of development.In this study used the dimensions of retaining wall with counterfort type,with a height of 3 meters, length per segment of 10 meters with 2 widthspedestal foundation as a parameter in the calculation of the base foundationthat is 2 meters wide and 1,2 meters. Quality of concrete used is 300 kg/cm2,equivalent to 24,090 MPa. From the calculation with two alternate dimensionsobtained pedestal foundation, the largest vertical force of 1306,264 KN, themoment of greatest in x direction 1065,5 KN.m, y direction of the greatestmoments of 457,471 KN.m.From the calculation shows that the width of the base foundationretaining wall will affect the ability of the wall withstand moments bolsters,thus widening the base foundation retaining wall then the ability walls resistroll will be greater and the need for the stake will be less, and vice versagetting smaller pedestal foundation walls, the ability to withstand rolling wallwill be smaller and the need for the stake will be many more.From the calculation shows that the width of the base foundationretaining wall has more influence on the ability of the wall withstand momentsbolsters, while the ability of the moments of withstand shear effect and the sameresult .